Efficacy of cupping therapy on pain outcomes: an evidence-mapping study - Wang, Liaoyao; Cai, Ziling; Li, Xuanlin; Zhu, Aisong (Frontiers in Neurology, 2023)
Objective: Cupping therapy is an ancient technique of healing used to treat a variety of ailments. An evidence mapping study was conducted to summarize the existing evidence of cupping therapy for pain-related outcomes and indicate the effect and the quality of evidence to provide a comprehensive view of what is known. Methods: PubMed, Cochrane Library, Embase and Web of Science were searched to collect the meta-analyses investigating the association between cupping therapy and pain-related outcomes. The methodological quality was assessed by using the AMSTAR 2 tool. Significant outcomes (P<0.05) were assessed using the GRADE system. The summarize of evidence is presented by bubble plots and human evidence mapping.Results: Fourteen meta-analyses covering 5 distinct pain-related conditions were identified and assessed for methodological quality using the AMSTAR 2, which categorized the quality as critically low (36%), low (50.0%), moderate (7%), and high (7%). In accordance with the GRADE system, no high-quality evidence was found that demonstrates the efficacy of cupping therapy for pain-related outcomes. Specifically, for neck pain, there were two moderate-quality, four low-quality, and two very low-quality evidences, while only 1 very low-quality evidence supports its efficacy in treating herpes zoster and 1 low-quality evidence for chronic back pain. Additionally, for low back pain, there were 2 moderate-quality, 1 low-quality, and 4 very low-quality evidences, and for knee osteoarthritis, 3 moderate-quality evidence suggest that cupping therapy may alleviate pain score.The available evidence of very low to moderate quality suggests that cupping therapy is effective in managing chronic pain, knee osteoarthritis, low back pain, neck pain, chronic back pain and herpes zoster. Besides, it represents a promising, safe, and effective non-pharmacological therapy that warrants wider application and promotion.